Resistance of Acanthamoeba to classic DNA extraction methods used for the diagnosis of corneal infections. Issue 1 (26th October 2007) - Goldschmidt, P; Degorge, S; Saint-Jean, C; Year, H; Zekhnini, F; Batellier, L; Laroche, L; Chaumeil, C
Abstract : Aims: Sensitive diagnosis of Acanthamoeba infections may prevent the clinical condition from becoming worse. In order to improve the diagnosis tool performances, we studied the implication of the DNA extraction procedures on the detection of Acanthamoeba by real-time PCR. Methods: Acanthamoeba cysts mixed with a tag virus were processed according to different DNA preparation procedures: heat, Proteinase K (ProtK), alkali lysis, QIAmp kit®, MagNA Pure (DNA Mini kit, MagNA Pure® Nucleic Acid isolation kit), ProtK+QIAmp and ProtK+MagNA Pure. Parasite-DNA loads were assessed by real-time PCR. Results: The results show that the structures of Acanthamoeba cysts are resistant to reagents releasing the DNA from other cells and viruses. Heat, NaOH or ProtK did not allow the DNA extraction yields to be assessed or the inhibitors to be eliminated The QIAmp and the MagNA Pure partially improved the sensitivity of the PCR and eliminated the inhibitors. A significant increase in positive results was obtained with a ProtK treatment before commercial extraction kits. ProtK+MagNA Pure yielded the highest rates of positivity. Conclusion: To minimise false negative results, the nucleic-acid based Acanthamoeba diagnosis requires, first, the efficient lysis of cysts (without affecting the DNA) to make the DNA available for extraction and amplification, and, second, the elimination of PCR inhibitors. A significant increase in the detection rates is obtained by adding a ProtK treatment (10 min at 56°C) before the commercial procedures. ProtK+MagNA Pure yielded the best results in 30 min, followed by ProtK+QIAmp (150 min).